Factors associated with unfavorable perinatal impacts in pregnants with oligohidramnios in Vitarte Hospital, 2016-2019 - Cotera-Abad, Gabriela T. (2021)
Introduction: Oligohydramnios is the deficient presence of the volume of amniotic fluid; it has a world frequency of approximately 0.5% to 5.5%, as a condition that complicates pregnancy. It has been associated with an increased risk of perinatal morbidity and mortality. Objective: Identify the factors associated with unfavorable perinatal repercussions in pregnant women with oligohydramnios at the hospital de Vitarte, period 2016-2019. Materials and methods: An analytical retrospective study of case and control was carried out. The population studied were pregnant women with diagnostic of oligohydramnios, by the ILA method of less than 5cm, attended at the Gynecology-Obstetrics hospitalization service at the hospital de Vitarte, during the period 2016-2019; made up of 97 cases and controls (1: 1). The cases were those that had unfavorable perinatal results. The chi-square test was used in the bivariate analysis, with a significance level of 0.05. The ORs with a 95% Confidence Interval were calculated through the SPSS program. Results: Newborns with unfavorable repercussions presented in the 47%. The most frequent type of delivery was by caesarean section (76%) and showing an association with the resulting adverse perinatal (OR = 2.25; 95% CI = 1.21 – 4.19; p = 0.009). No significant differences were found with maternal sociodemographic variables, start of labor, gestational age, number of prenatal controls, parity, maternal comorbidity and sex of the newborn. Conclusions: Perinatal morbidity and mortality is frequent in pregnant women diagnosed with oligohydramnios. Cesarean delivery is a factor associated with unfavorable perinatal repercussions. The indication for caesarean section is unnecessary only due to the finding of oligohydramnios, this should be guided by the underlying pathology.